P03 The effects of haem on perfusion parameters and the activation of innate immune system in human kidneys during ex vivo normothermic machine perfusion. (22nd July 2022) - Elliott, TR; Hosgood, SA; Jordan, NP; Nicholson, ML
Abstract: Introduction: Normothermic machine perfusion (NMP) of kidneys, using an oxygenated red blood cell (RBC) based solution has been developed to restore cellular metabolism and minimise effects of cold ischaemia. During NMP RBCs become damaged releasing haem activating inflammatory signalling pathways. This study aimed to measure levels of haem during NMP and determine the association with perfusion parameters and transcriptional changes in gene expression. Methods: Levels of haem were measured in the perfusate before and after 1h NMP in 43 transplanted and 15 research human kidneys. Levels of haem were correlated with the age of RBCs and parameters during NMP. Human research kidneys were used to examine the changes in transcriptional gene expression using Nanostring nCounter technology. Results: In transplanted and research kidneys, levels of haem increased significantly (P <0.05) during NMP. Older units of pRBCs were associated with higher levels of haem, pre-/post-NMP. High levels of haem were associated with higher levels of potassium and lactate but not functional parameters during NMP. NanoString analysis demonstrated significant upregulation of 17 differentially expressed genes including those associated with apoptosis, inflammation and oxidative stress. qPCR analysis of targeted genes demonstrated increased expression of FOS (P<0.0001), IL-6 (P=0.0001), JUN (P=0.0001) and TLR-4 (P=0.035). Conclusion: Older units of RBCs contain high levels of haem which increases during NMP. Although, this did not affect perfusion parameters, transcriptional analysis demonstrated significant upregulation of genes involved with apoptotic, inflammatory and oxidative pathways. Activation of these pathways may be associated with high levels of haem. Take-home message: Older units of packed red blood cells release increased levels of haem during normothermic machine perfusion of kidneys. Higher levels of haem are linked to increased activation of damage pathways.